Effects of Microclimatic Parameter on Tea Leaf Production in Different Tea Estates, Bangladesh - Ali, M; Uddin, MN; Mobin, MN; Saha, N (Journal of Environmental Science and Natural Resources, 2025)
The editorial team of Journal of Environmental Science and Natural Resources hereby announces the withdrawal of the published manuscript titled "Effects of Microclimatic Parameter on Tea Leaf Production in Different Tea Estates, Bangladesh", authored by Ali, M., Uddin, M. N., Mobin, M. N., and Saha, N. (2014), which was published in Volume No. 7, Issue No. 1, Page No. 183-188, DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22168. This decision was made following a formal request from the authors due to unintentional duplicate submission, which came to light after publication. After careful consideration and in accordance with the journal’s editorial policies and guidelines, the manuscript has been formally withdrawn from the published record. We acknowledge the inconvenience this may cause to our readers and stakeholders and reaffirm our commitment to maintaining the integrity and transparency of the scientific publication process.